An Analysis Of The Most Difficult Part In Structure And Written Expression Section In Toefl Test - hanifah hanifah (Universitas KH. A. Wahab Hasbullah, 2019)
This article aims to describe materials existing in structure and written expression in ITP TOEFL test and parts which are difficult for students when they answer the questions and it explains why they make some errors in answering the questions too. TOEFL books, questionnaire, and interview became the data source of this research. This research randomly took 30 students who had finished their TOEFL preparation class as the subject. The results of this research are that there are nine materials that must be mastered by students in mastering structure and written section; 1) sentence 2) Subject and verb agreement, 3) noun, 4) verb form, 5) dependent clauses, 6) coordinate conjunction, 7) inversion, 8) comparison degree, 9) word order, and the three most difficult parts are subject verb agreement, dependent clauses, and inversion. The common mistake done in answering questions is that they are not careful enough with the sentence’s structure and they have not known some uncommon structure yet, especially in inversion and dependent clauses (reducing, omitting, and abridgment)